Development of a Recombinant Fusion Vaccine Candidate Against Lethal Clostridium botulinum Neurotoxin Types A and B - Eun-Sun Choi; Seong-Wook Pyo; So-Hyeon Kim; Jun-Ho Jeon; Gi-Eun Rhie; Mi-Ran Yun; Hwajung Yi; Yoon-Seok Chung (Vaccines)
Background: Botulinum neurotoxins (BoNTs), produced by Clostridium botulinum, are potent protein toxins that can cause botulism, which leads to death or neuroparalysis in humans by targeting the nervous system. BoNTs comprise three functional domains: a light-chain enzymatic domain (LC), a heavy-chain translocation domain (HCN), and a heavy-chain receptor-binding domain (HCC). The HCC domain is critical for binding to neuronal cell membrane receptors and facilitating BoNT internalization via endocytosis. Accordingly, it may serve as a vaccine candidate, inducing anti-BoNT-neutralizing antibodies in animals. Here, we aimed to develop a vaccine capable of simultaneously defending against both BoNT/A and B. Methods: We combined the HCC domains of botulinum neurotoxin type A (BoNT/A) and botulinum neurotoxin type B (BoNT/B) in Escherichia coli to produce a recombinant protein (rHCCB-L-HCCArHCcB) that offers dual protection against both toxins by inhibiting their receptor binding. To evaluate the efficacy of the vaccine, mice were immunized intramuscularly with rHCCB-L-HCCA plus alum thrice at 2-week intervals, followed by the assessment of immunogenicity and protective efficacy. Results: The antibody titer in mice immunized with rHCCB-L-HCCA was significantly higher than that in mice immunized with alum alone, protecting them from the lethal challenges of BoNT/A (105 50% lethal dose, LD50) and B (103 LD50). Conclusion: These findings suggest that rHCCB-L-HCCA may simultaneously be an effective vaccine candidate against BoNT/A and B.